Risk Factors of Children Under Five Malnutrition in Kamanasa Village, Malaka Tengah Subdistrict - Ermelinda T. W. Mango; Anna Henny Talahatu; Marselinus Laga Nur (Lontar : Journal of Community Health, 2020)
Malnutrition is a condition of nutritional deficiencies due to lack of nutrients such as protein, carbohydrates, fats, and vitamins needed by the body. Several factors affect malnutrition, including the level of mother’s education, family income level, knowledge level of energy sufficiency, level adequacy of protein, and infectious diseases. This study aimed to analyze the risk factors that affect the incidence of malnutrition. This study is an observational analytic, with a case-control design, the sample size is 42 respondents for cases, and 42 respondents for controls. Dependent variables in this research are the incidence of malnutrition level, level of family income, mothers' level of knowledge, level of energy sufficiency, level of protein adequacy, and infectious diseases. Data analysis used chi square and simple logistic regression. The result showed that five variables affect the incidence of malnutrition. These five variables are family income (p= 0,000; OR-6,400), the level of mother’s knowledge (p=0,000; OR=5,577), the level of energy sufficiency (p=0,000; OR=7,333), protein adequacy level (p=0,000; OR=3,676), and infectious diseases (p=0,000; OR =3,600). Health staff should provide a comprehensive explanation about balanced nutrition in the family and distribute health promotion media, such as leaflets to families.